Possibility of Generation and Amplification to High Power of Ultraviolet Ce:LiCAF Laser Short Pulses - Minh, Pham Hong; Duong, Pham Van; Thong, Pham Huy; Khanh, Do Quoc; Hung, Nguyen Dai; Sarukura, Nobuhiko (Communications in Physics, 2016)
We review the recent progresses in generation and amplification of ultraviolet laser emissions using Ce$^{3 + }$:LiCaAlF$_{6}$ (Ce:LiCAF) material as a gain medium. Basing on comparative studies, we have investigated improvements and proposed possibilities to generate and amplify ultraviolet short-pulse Ce:LiCAF laser emission to high peak power of terawatt.